2020
DOI: 10.1021/acsomega.0c02007
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Nanomaterials Approach: Influence of Culture Conditions on the Stability and Antimicrobial Activity of Silver Nanoparticles

Abstract: Silver nanoparticles (AgNPs) as antimicrobial agents have been extensively studied. It is generally assumed that their inhibitory activity heavily depends on their physicochemical features. Yet, other parameters may affect the AgNP traits and activity, such as culture medium composition, pH, and temperature, among others. In this work, we evaluated the effect of the culture medium physicochemical traits on both the stability and antibacterial activity of AgNPs. We found that culture media impact the physicoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 81 publications
0
24
0
Order By: Relevance
“…2 ). The stability of the nanoparticles as colloid is very important, as unstable NPs will not be able to disperse homogenously, which may effect on their antibacterial properties and reducing the efficacy 31 , 36 . Therefore, the polidyspersity index (PdI) was used as a value which show the stability of the nanomaterial.…”
Section: Resultsmentioning
confidence: 99%
“…2 ). The stability of the nanoparticles as colloid is very important, as unstable NPs will not be able to disperse homogenously, which may effect on their antibacterial properties and reducing the efficacy 31 , 36 . Therefore, the polidyspersity index (PdI) was used as a value which show the stability of the nanomaterial.…”
Section: Resultsmentioning
confidence: 99%
“…Only 0.2% of the silver contained in the Argovit™ formulation is released as ions. From a sample of 10 μg/mL AgNPs left under stirring for 24 h, 0.024 μg/mL of Ag + was quantified in solution by inductively coupled plasma atomic emission spectroscopy (ICP-OES) [ 55 ]. The larger stability of this formulation that avoids silver ion release is associated with the high amount of polyvinylpyrrolidone (PVP) used as a coating agent [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on our results, we have recommended to obtain a circumspect selection of the green extracts used for the synthesis of nanoparticles, and suggested that a comprehensive screen of the products should be carried out prior to their applications to delineate their behavior in the presence of living systems. Based on today’s nanotechnology results, combining the available methods of biology, chemistry and material sciences, more complex investigations can be carried out [ 162 , 163 ]. Using such an approach, systematic examinations regarding AgNP aggregation behavior with simultaneous measurements of its effect on biological activity can be performed to offer new frontiers to preserve nanoparticle toxicity by enhancing colloidal stability [ 70 ].…”
Section: Synthesismentioning
confidence: 99%